SEGA (SPEAKING ENGLISH GAMES) MEDIA FOR MENTALLY DISABLE STUDENT OF JUNIOR HIGH SCHOOL AT SLB MUHAMMADIYAH JOMBANG - Ulfa Wulan Agustina; Iin Baroroh Ma'arif; Luluk Choirun Nisak Nur; Riska Avianti (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2024)
The aim of this research is to design learning media named SEGA (Speaking English Games) to help mentally disable students of 7thgrade Junior High School at SLB Muhammadiyah Jombang. This research focuses on studentâ€™s vocabulary mastery by using games as learning media. The research method used is Research and Development (R&D). This development used ADDIE model which consist of: Analysis, Design, Development, Implementation, and Evaluation. The research result was got through the process of need analysis, material validation, media validation, and studentsâ€™ responses. To collect the data, researcher used observation, interviews, and questionnaire. The result average material validation got 92% and it was in â€œVery Goodâ€ category, while the result average media validation got 92,5% and it was in â€œVery Goodâ€ category. Subject of this research was mentally disable students in 7thgrade Junior High School at SLB Muhammadiyah Jombang. The studentsâ€™ responses of tried out result got 95% was in â€œVery Goodâ€ category. Based on those result, it can be concluded that SEGA (Speaking Eglish Games) learning media is feasible or deserved to be used as learning media to improve studentsâ€™ vocabulary mastery. KEYWORDS: Learning media, SEGA, Mentally disable student, Junior high